Educational Supervision System In The Formation Of Student Discipline In Raudhatul Athfal - Salsabilla, Tiara; Fadilah, Raghil; Septiyani; Edwid Nivacindera, Syellen; Permana, Hinggil (The Faculty of Education and Teaching Training, 2024)
This study aims to determine the educational supervision system in shaping student discipline in Raudhatul Athfal (RA). Supervision in education has an important role in improving the quality of education through evaluation and control of conditions to support the achievement of educational goals. This research examines how the supervision system is implemented in RA Al Fajr to support optimal character building and student discipline. The research method used in this research is descriptive qualitative with the type of case study research. While the data collection techniques use observation, interviews and documentation. The results of the research on the educational supervision system play an important role in shaping student discipline at RA Al Fajr because through good supervision, students can be directed and fostered to comply with applicable regulations. Not only that, supervision is also carried out on the curriculum that has been prepared. The conclusion that can be drawn from this research is that discipline is very important for personal development, starting from childhood. Teaching discipline involves creating a disciplined environment at home and school. Observations and interviews show the importance of discipline in students and teachers.